Diversification of Taro Commodity-Based Derivative Products To Increase Community Income in Gunajaya Village, Tasikmalaya District - Heryadi, D. Yadi; Nurcahya, Intan; Nirwanto, Yogi (Pascasarjana Universitas Mataram, 2024)
The constraints of local food development are the lack of derivative products that are easily accepted, accessible to the community and the implementation is not optimal. The purpose of Community-Based empowerment with the scope of Community Partnership Empowerment (PbM-PkM) is to empower the community through partners KWT Teratai and Poktan Kertaraharja III Gunajaya Village, Manonjaya District, Tasikmalaya to increase the diversification of derivative products from Talas Pratama to increase community income. This activity was carried out from May to December 2024. Gunajaya Village is the centre of Talas Pratama producers with productivity/ha around 30-40 tonnes, but most of it is sold raw so that the added value is low. There is an effort to diversify Talas Pratama into several derivative products, but until now it is still constrained by limited knowledge and skilled personnel to process products. This activity uses methods of socialisation, counselling, product processing diversification training, evaluation, grant assistance and mentoring. This activity has had an impact on the socio-economic conditions of the participants in the form of psychological assets, informational assets, organizational assets, material assets, financial assets, and human assets. Partners have produced various taro derivative products including taro flour which is processed into Cilok, Crackers, Bolu, Perkedel